Treatability Statements in Serious Illness: The Gap Between What is Said and What is Heard - Batten, Jason N. (Cambridge quarterly of healthcare ethics, 2019)
Empirical work has shown that patients and physicians have markedly divergent understandings of treatability statements (e.g., “This is a treatable condition,” “We have treatments for your loved one”) in the context of serious illness. Patients often understand treatability statements as conveying good news for prognosis and quality of life. In contrast, physicians often do not intend treatability statements to convey improvement in prognosis or quality of life, but merely that a treatment is available. Similarly, patients often understand treatability statements as conveying encouragement to hope and pursue further treatment, though this may not be intended by physicians. This radical divergence in understandings may lead to severe miscommunication. This paper seeks to better understand this divergence through linguistic theory—in particular, H.P. Grice’s notion of conversational implicature. This theoretical approach reveals three levels of meaning of treatability statements: (1) the literal meaning, (2) the physician’s intended meaning, and (3) the patient’s received meaning. The divergence between the physician’s intended meaning and the patient’s received meaning can be understood to arise from the lack of shared experience between physicians and patients, and the differing assumptions that each party makes about conversations. This divergence in meaning raises new and largely unidentified challenges to informed consent and shared decision making in the context of serious illness, which indicates a need for further empirical research in this area.